Ուսանողների ուսումնական սթրեսների առաջացման պատճառները և օպտիմալացման ուղիները - Անահիտ Ղազարյան (ՀՀ ԳԱԱ հրատ.)
В статье обсуждается негативные воздействия и последствия стрессов, указываются способы устранения. This article discusses the negative causes and consequences of students’ academic stress and gives the ways of eliminating it. The relevance and importance of the article is conditioned by the above mentioned issues.
Keywords: Psychology; Education